Teaching portuguese as a non-native language: an experience of teaching-learning and host - Ramos, Karin Adriane Henschel Pobbe [UNESP]; Nascimento, Eric Santos do [UNESP] (Unesp-faculdade Ciencias & Letras, 2021)
This paper aims to report an experience of teaching Portuguese as an additional language to host a family of Libyans and Algerians who currently live in the city of Marilia, in the countryside of the State of Sao Paulo. The described process has been developed as part of scientific initiation research, with a grant from the National Council for Scientific and Technological Development (CNPq), by a student of Languages at a public university located in the countryside of the State of Sao Paulo. The theoretical contribution is based on an intercultural approach to language teaching. The final considerations point to the need to share these experiences to strengthen the area of Portuguese as a Non-Native Language.
Keywords: Portuguese Non-Native Language; Host; Experience report